Hukum Keluarga Islam ala Negara: Penafsiran dan Debat atas Dasar Hukum Kompilasi Hukum Islam di Kalangan Otoritas Agama dan Ahli Hukum - Euis Nurlaelawati (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2016)
This  article  explores  the  reaction  to  and  criticism  of  the reform  aspects  introduced  in  the  kompilasi  which  have  arisen  among Indonesian Muslim, the ulama of two biggest Muslim organizations in particular and the legal apparatus and scholars. It addresses the issue by looking at specific questions relating to the rationales ofthe reforms. Deploying  socio-historical  legal  approach,  it  displays  the  reform aspects, the arguments and the tendency in their criticism and debate, as well as the key concepts and interpretations of Islamthey have used. It argues that these ‘ulama have distinct and differentways of looking at the reforms, which is intersected with the general attitude of these two organizations in deducting the laws of Islam. Thisarticle stresses that  the  reforms  have  always  not  been  accepted  in  their  whole  by Muslim  society  and  that  the  Islamic  rationales  of  the  reforms  have often  been  deemed  inappropriate,  demonstrating  in  this  sense  the harsh debate between the use of fiqhand Qur’anand between the use of Islamic classical law and the incorporation of  adatlaw as their sources and bases. Further it shows that, although the proposal of reforms was proclaimed  to  be  based  on  the  societal  growing  needs  and demands, they remained to be objects of criticism and debates from such certain groups of Muslims and legal apparatus who argued to also base their criticism on the needs of society.